The Romanian Society of Internal Medicine's Choosing Wisely Campaign - Delcea Caterina; Badea Camelia; Jurcut Ciprian; Purcarea Adrian; Sovaila Silvia; Weiss Emma; Alistar Elena; Balan Horia; Baicus Cristian (Sciendo, 2019)
Quality of care in medicine is not necessarily proportional to quantity of care and excess is often useless or even more, potentially detrimental to our patients. Adhering to the European Federation of Internal Medicine's initiative, the Romanian Society of Internal Medicine (SRMI) launched the Choosing Wisely in Internal Medicine Campaign, aiming to cut down diagnostic procedures or therapeutics overused in our country. A Working Group was formed and from 200 published recommendations from previous international campaigns, 36 were voted as most important. These were submitted for voting to the members of the SRMI and posted on a social media platform. After the two voting rounds, the top six recommendations were established.